Measuring child exposure to violence and mental health reactions in epidemiological studies: challenges and current issues - Duarte,Cristiane Seixas (2009)
This paper examines challenges and current issues involved in measuring exposure to different types of violence which are associated mental health problems in children and adolescents. Standardized measures suitable for epidemiological studies, selected based on their relevance in the current literature, are briefly described and commented. The assessment of child's exposure to violence may focus on a specific event (e.g., kidnapping), a specific context (e.g., war) or even of a certain type of exposure (e.g., intrafamilial physical violence). The assessment of child mental health after exposure to violence has traditionally focused on posttraumatic stress disorder (PTSD) - most frequently measured through non-diagnostic scales. However, other mental health reactions may be present and screening as well as diagnostic instruments which may be used to assess these reactions are also described. Two issues of emerging importance - the assessment of impairment and of traumatic grief in children - are also presented. Availability of culturally appropriate instruments is a crucial step towards proper identification of child mental health problems after exposure to violence.